Aerodynamics Study Of Tubercle Effect On NACA4412 Airfoil - Enso, Ennelyn Novema (Universiti Sains Malaysia, 2017)
Aerodynamics Study of Tubercle Effect on NACA4412 Airfoil The purpose of this research is to study the aerodynamics characteristics of NACA4412 airfoil with tubercle effect on its leading edge. The study was performed on three different leading edges of the airfoil; leading edge without the tubercles, leading edge with spherical tubercles and leading edge with continuous spherical tubercles. The study focuses on the effect of the spherical tubercles on aerodynamics lift and drag characteristics of the NACA4412 airfoil. The experiment was performed by using the wind tunnel in the aerodynamics laboratory in Universiti Sains Malaysia. The result was obtained, compared and discussed further in the thesis.